2015
DOI: 10.1007/s11101-015-9404-6
|View full text |Cite
|
Sign up to set email alerts
|

Chemical constituents and biological activities of South American Rhamnaceae

Abstract: Secondary metabolites have diverse functions into plants. These functions are products of the coevolution which result in synthesis of constitutive and/or induced chemical defense generated for protection against to different phytopathogenic attack. Many phytochemical studies are biodirected with the aim of finding biopesticides of botanical origins. Some taxa of Americas such as Rhamnaceae family are toxic to insects, fungi and several bacteria strains, and these effects has been associated with the presence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…B. bassiana and V. lecanii is making them promising in effective pest management strategies (Ali et al, 2018). Even if a large number of studies have focused on the biological activity of biorational products with an insecticidal action on target organisms (Alarcon and Cespedes, 2015), studies concerning toxicological studies and their effects on non-target organisms are scant (Shao and Zhang, 2017). Moreover, the synthesized findings lack naturally derived products with both pesticidal and growthpromoting effects with ensured environmental safety.…”
Section: Introductionmentioning
confidence: 99%
“…B. bassiana and V. lecanii is making them promising in effective pest management strategies (Ali et al, 2018). Even if a large number of studies have focused on the biological activity of biorational products with an insecticidal action on target organisms (Alarcon and Cespedes, 2015), studies concerning toxicological studies and their effects on non-target organisms are scant (Shao and Zhang, 2017). Moreover, the synthesized findings lack naturally derived products with both pesticidal and growthpromoting effects with ensured environmental safety.…”
Section: Introductionmentioning
confidence: 99%
“…et Hook) (Rhamnaceae) is a shrub or small tree distributed throughout the central‐southern zone of Chile . Previous studies of the aerial part of the plant have reported a set of pentacyclic triterpenes and alkaloids with a benzylisoquinoline skeleton . In this family, the presence of compounds such as polyphenols, triterpenes, aromatics, flavonoids, and cyclopeptide, aporphines and benzylisoquinoline alkaloids is characteristic .…”
Section: Introductionmentioning
confidence: 99%
“…1 Previous studies of the aerial part of the plant have reported a set of pentacyclic triterpenes and alkaloids with a benzylisoquinoline skeleton. [2][3][4] In this family, the presence of compounds such as polyphenols, triterpenes, aromatics, flavonoids, and cyclopeptide, aporphines and benzylisoquinoline alkaloids is characteristic. 2 Different biological activities have been attributed to plants of this family, and particularly to the alkaloids.…”
Section: Introductionmentioning
confidence: 99%
“…However, to date, there are no reports regarding the proposed mechanism of AChE inhibition by ceanothanes triterpenes. It is known that the Rhamnaceae family is a rich source of pentacyclic triterpenes, particularly with the ceanothane skeleton [ 28 , 39 ]. These inhibitors had low micromolar IC 50 (0.126–0.188 µM) values for AChE ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%